Asuhan Kebidanan Berkelanjutan Terhadap By. Ny. F Di Pmb Saripah, S.St Dengan Pemberian Terapi Temu Kunci Untuk Mengurangi Batuk Pilek Pada Bayi Usia 14 Hari - Susilowati Susilowati; Novita Sari; Dwi Yuliarti; Endang Sukosih; Siti Aminah (Journal on Education, 2025)
Continuity of care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborn care and family planning services that connect the health needs of women in particular and the personal circumstances of each individual. Comprehensive care is an examination that is carried out completely with a simple laboratory examination and counseling. Comprehensive midwifery care includes a place for continuous examination activities including pregnancy midwifery care, delivery midwifery care, postpartum midwifery care and newborn midwifery care and family planning acceptors. Pregnancy care prioritizes continuity of care, which is very important for women to get services from the same professional or from a small team of professionals, because that way the development of their condition will be monitored well at all times, besides they will also trust and be open because they feel they already know the caregiver. The type of research used is descriptive, with a case study approach. The sample used was By.Ny. F. After providing care, comprehensive midwifery care has been provided starting from pregnant women, childbirth, postpartum, babies and the results are normal pregnancy, normal childbirth, babies with the provision of temu kunci therapy which is considered effective in reducing coughs and colds, and up to family planning. There is no gap between theory and cases in Comprehensive Midwifery Care in By. Mrs. F